Analysis of the Effect of Different Packaging Conditions on Cucumber Flavor Based on Gas Chromatography-Ion Mobility Spectrometry Technology - Fucheng WANG; Si MI; Jinsong LI; Yuhang WANG; Xianghong WANG (Shipin gongye ke-ji, 2022)
In order to investigate the influence of different package materials on the flavor quality of cucumbers during postharvest storage at (13±2) ℃, three different treatments consisting of perforated polyethylene packaging bags 0.03 mm in thickness, perforated polyethylene 0.07 mm packaging bags in thickness and no package were evaluated. The volatile organic compounds (VOCs) in the cucumbers were analyzed by using chromatography-ion mobility spectrometry (GC-IMS), and multivariate analysis was then performed. The results showed that a total of 60 volatiles were identified in the cucumber samples, which could be generally classified into 2 hydrocarbons, 14 alcohols, 13 aldehydes, 13 ketones, 8 esters, 5 acids, 3 ethers, one pyrazine, and one furan compound. A clear separation between the experimental groups was achieved in the multivariate analysis. A panel of 19 volatile compounds with P<0.05 and VIP score > 1 were suggested as potential markers for the discrimination of cucumbers treated with different packing materials, these 19 volatile compounds are acetone, 3-hydroxybutan-2-one, 3-pentanone, 2,3-butanedione, butanone, methyl isobutyl ketone, 2-pentanone, 2-hexanone, methylpropanal, butyraldehyde, butanal, pentanal, 3-methylbutanal, 1-propanol, 3-methyl-3-buten-1-ol, 2-methylbutan-1-ol, isobutanol, pentan-1-ol, 1-butanol, and ethyl acetate. During storage, the aldehydes of the main aroma of unpackaged cucumber decreased more obviously, and produced some ketones, esters, ethers, and other volatile metabolites, indicating that the loss of the unique aroma of cucumber in unpackaged was serious, while the aldehydes of the main aroma of cucumber in perforated passive modified atmosphere packaging decreased slowly, and the substances such as 3-hydroxy-2-butanone produced due to microbial growth increased less. Overall, perforated polyethylene 0.07 mm in thickness is recommended as a relatively efficient material to maintain the flavor quality of cucumbers. The findings were expected to facilitate the development and application of these package materials in the large-scale storage of cucumbers.